Scale‐ and time‐dependent effects of fertilization, mowing and dominant removal on a grassland community during a 15‐year experiment - Lepš, Jan; Wan, Shiqiang (The Journal of applied ecology, 2014)
Multiple land‐use change drivers affect, in most cases negatively, the biodiversity in species‐rich meadows. Empirical data that can help to disentangle the effects of individual drivers and quantify the time required for a biodiversity response are seldom available. Management decisions are often based on short‐term experiments or observational data. A 15‐year field experiment, comprising a factorial combination of fertilization, mowing and removal of the dominant species Molinia caerulea, was established in an oligotrophic wet meadow in Czech Republic. Each of the eight factorial combinations was replicated three times. Percentage cover for all species was monitored annually in 1‐m² plots and species' presence recorded in each cell of a continuous square grid of 25 cells (0·1 × 0·1 m each). These data enabled various scale‐dependent estimates of species richness. The species composition of individual treatment combinations diverged over time, particularly at the start of the experiment, and by the latter stages resembled various typical grassland communities from the surrounding landscape. Fertilization had the most pronounced effect, leading to a sharp decrease in species richness, most rapidly at the smallest spatial scale. Mowing had on average a positive effect on species richness and led in most cases to spatially homogeneous species composition. The removal of Molinia had a positive effect on species richness, especially in unmown unfertilized plots. The effects of each factor were dependent on the combination of the other two factors, and also on time, with some effects continuously increasing throughout and some diminishing by the end of the experiment. The process of competitive exclusion with fertilization and cessation of mowing was, in some treatment combinations, rather slow. Synthesis and applications. Land‐use change drivers act in combination, and their effects on the structure of species‐rich wet meadows are dependent on both the temporal and spatial scales considered. Short‐term experiments might underestimate the response of vegetation and thus provide erroneous conservation recommendations. Mowing was only effective in preventing species richness decline caused by fertilization in the short term. The presence of a single dominant species can modify the effectiveness of conservation measures.